2016
DOI: 10.5539/ijef.v8n3p189
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Budget Deficit on Private Consumption inWAEMU Countries: Evidence from Pooled Mean Group Estimation

Abstract: This study empirically investigates the impact of budget deficit on private consumption in seven member countries of the West African Economic and Monetary Union (WAEMU), namely Benin, Burkina Faso, Côte d'Ivoire, Mali, Niger, Senegal and Togo. It applies the pooled mean group estimation method to annual data covering the period 1970 to 2013. The results show that budget deficit and per capita GDP have long run positive effects on household consumption whereas inflation rate is detrimental to private consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…With the coefficient of -0.192, private consumption will significantly decrease by 0.19 percent as a result of a 1 percent increase in government spending in Sub-Sahara African countries. Thus, fiscal policies that promote excessive government spending might have adverse impacts on private consumption (Keho 2016). Again, it was apparent from the results that government spending maintained its expected signs in the short run just like in the long run.…”
Section: Mean Group and Pooled Group Estimatesmentioning
confidence: 92%
See 2 more Smart Citations
“…With the coefficient of -0.192, private consumption will significantly decrease by 0.19 percent as a result of a 1 percent increase in government spending in Sub-Sahara African countries. Thus, fiscal policies that promote excessive government spending might have adverse impacts on private consumption (Keho 2016). Again, it was apparent from the results that government spending maintained its expected signs in the short run just like in the long run.…”
Section: Mean Group and Pooled Group Estimatesmentioning
confidence: 92%
“…His results exhibited the evidence of Keynesian debt non-neutrality in Zimbabwe. Also, Keho (2016) noted that, in the longrun, budget deficit and GDP per capita have significant positive effects on private consumption, whilst inflation is detrimental to private consumption in the West African Economic and Monetary Union (WAEMU) member countries. This implies that limiting the size of the budget deficits might have a deleterious effect on the development of WAEMU member countries.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The long-run slope homogeneity hypothesis is tested via a Hausman test, where under the null hypothesis, the difference in the estimated coefficients between the MG and PMG is not significantly different and PMG is not significantly different and PMG estimators are consistent and more efficient than MG estimators (Pesaran et al, 1999). Adusah-Poku (2016), Kehoy (2016), Bangake and Eggoh (2012) and Ndambendia and Njoupouognigni (2010) used the PMG technique for estimation of their econometric models.…”
Section: Oda and Economic Growthmentioning
confidence: 99%
“…They concluded that REH fails in Pakistan due to the limitless horizon and lack of money. Keho (2016) discovered that in the long run, the budget deficit and GDP per capita have large positive effects on private consumption, but inflation has a negative impact in the West African Economic and Monetary Union (WAEMU) member nations, Ofori-Abebrese and Pickson (2018) studied five Sub-Sahara African countries: Botswana, Ghana, Gambia, Nigeria, and Kenya between 1981 and 2014. They investigated the evidence of REH using the panel Autoregressive Distributed Lag Approach (ARDL).…”
Section: Introductionmentioning
confidence: 99%